2022
DOI: 10.3390/su14148380
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers from Physical Education: Differences between Ireland and Spain in Teaching Personal and Social Responsibility

Abstract: The present study aimed to analyse and contrast the experiences of six Preservice Physical Education Teachers (onwards PPET) from two different socio-demographic contexts, Spain and Ireland, regarding the use of Teaching Personal and Social Responsibility (henceforth TPSR) during their work placement. The sample consisted of six students aged between 21 and 25 years (three boys and three girls), in their final year of their bachelor’s degree, who had completed their work placement within the education pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Finally, as future work, the hybridization of methodologies that provide an optimal result due to their multiple possibilities [76] can be considered, for example, combining the current intervention with the personal and social responsibility model [77] that has provided very good results in terms of variables related to emotional well-being [27,40] or even interventions where others factors that are deemed to be important for life have been investigated. These factors could be resilience as a capacity to overcome adversity [78], in addition to working towards life satisfaction, a variable that has shown a high correlation with the development of self-awareness [79], which was the main objective of the program.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Finally, as future work, the hybridization of methodologies that provide an optimal result due to their multiple possibilities [76] can be considered, for example, combining the current intervention with the personal and social responsibility model [77] that has provided very good results in terms of variables related to emotional well-being [27,40] or even interventions where others factors that are deemed to be important for life have been investigated. These factors could be resilience as a capacity to overcome adversity [78], in addition to working towards life satisfaction, a variable that has shown a high correlation with the development of self-awareness [79], which was the main objective of the program.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…It is considered fundamental that AB-based programmes carry out specific training and follow-up of classes, because the teachers who apply the methodology are not usually teachers specialized in PE and need greater support to specify the resources and strategies to be used [18,25]. Regarding the use of TPSR, studies such as the one by Manzano-Sánchez et al [65] indicate that not only is adequate initial training necessary [4,7], but continuous training and monitoring must also be carried out, especially with new teachers. Finally, it is suggested that future studies use more objective measures to assess physical activity-related FOI, such as accelerometers or heart rate monitors, to complement the observational analysis of students' and teachers' behaviours.…”
Section: Discussionmentioning
confidence: 99%